Craig’s Anti–Platonism, Lowe’s Universals, and Christ’s Penal Substitutionary Atonement - Smith, R. Scott (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
William Lane Craig has defended nominalism as a kind of “anti–Platonism.” To him, Platonism is inimical to God’s aseity. More recently, he also has defended the penal substitution of Christ. However, he has not brought the two subjects into dialogue with each other. In this essay, I will attempt to do that by exploring the implications of two major types of nominalism, austere nominalism and trope theory, for the penal substitution. I will argue that nominalism will undermine the penal substitution of Christ. Instead, to try to preserve both his anti–Platonism and the penal substitution, a better alternative for Craig is to embrace E. J. Lowe’s immanent universals.